Wahdat al-Wujûd ‘Abd al-Karîm al-Jîlî - Ghozi Ghozi (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2013)
This article discusses the Islamic mysticism of ‘Abd al-Karîm al-Jîli, which is known as wahdat al-wujûd. Al-Jîli is one of Ibn ‘Arabî’s thought interpreters and commentators. In this case, al-Jîli provided Ibn ‘Arabî doctrine of theosophy more sophisticated. His effort is to present Ibn ‘Arabî’s doctrine more acceptable upon the frame of sharî‘ah. In fact, the effort to present different angles of the conception of wahdat al-wujûd. According to him, wahdat al-wujûd must be seen from a visioner and spiritual perspective. It is not be seen in a philosophical frame of thought as most of the modern western perspective. It. In addition, wahdat al-wujûd doctrine is built on the holy experience, which is based on sharî‘ah.